A Comment on Factor Price Equalisation - Samuelson, Paul A. (Review of Economic Studies, 1951)
Journal Article A Comment on Factor Price Equalisation Get access Paul A. Samuelson Paul A. Samuelson Cambridge, Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 2, 1951, Pages 121–122, https://doi.org/10.2307/2295740 Published: 01 July 1951